The 15 March 2019 Bezymianny Volcano Explosive Eruption and Its Products - Girina O.A.; Gorbach N.V.; Davydova V.O.; Melnikov D.V.; Manevich T.M; Manevich A.G.; Demyanchuk Yu.V. (My University, 2020)
Bezymianny Volcano is one of the most active volcanoes in Kamchatka and in the world. This paper describes the preparation, behavior, products, dynamics, and the geological effect of the March 15, 2019 explosive eruption of the volcano, which was predicted 6.5 h before it began. The sequence of eruptive events was analyzed using data provided by video and satellite-based monitoring of the volcano; the quantitative characteristics for the distribution of pyroclastic deposits were obtained in the information system “Remote Monitoring of Activity of Volcanoes in Kamchatka and the Kurile Islands”. The explosions lifted ash to heights of 15 km above sea level (up to 12 km above the volcano), the eruptive cloud was moving northeastward and east from the volcano, the main ashfall area was 210 400 km2, including 15 000 km2 on land. Apart from tephra, the eruption produced pyroclastic flows and pyroclastic surges covering an area of 30 km2. The total volume of explosive products is estimated as 0.1–0.2 km3. The eruptive rocks are calc-alkaline moderate-K basaltic andesites (SiO2 = 54.84–56.29 wt %), they are the most mafic among all rocks of the current Bezymianny eruption cycle.
Keywords: 38.37.25 Вулканология; Безымянный